Jaringan Fog untuk Pemantauan Real Time Kualitas Air Tambak Udang - Jimsan, Jimsan; Mardiawati, Mardiawati (Jurnal Teknologi Sistem Informasi dan Sistem Komputer TGD, 2023)
Effective and efficient monitoring of water quality conditions in shrimp ponds is crucial to enhance shrimp production. Therefore, this research discusses a water quality monitoring system that provides real-time data and information on pond water quality parameters using a Fog network. The monitored water quality parameters include dissolved oxygen (DO), temperature, and pH. The values of these parameters are obtained in real-time through sensors within the Fog network. The data is then transmitted and stored in a database on a web server. The parameter values for temperature, pH, and DO in the database are illustrated in the form of graphs, representing the current condition of water quality. The system can also automatically provide notifications and alerts regarding the current monitored water quality condition. This enables prompt action to be taken if the parameter values deviate from the normal threshold limits